Crip or Die? Gang Disengagement in the Netherlands. (October 2018) - Roks, Robert A.
Building on the growing body of research on gang desistance and disengagement, this article focusses on the departure of 20 members of the Dutch Rollin 200 Crips during three years of ethnographic fieldwork (2011–2013) in a small neighborhood in the Dutch city of The Hague. In this article, I retrace the process of gang disengagement from the onset of conflicts within the gang, the growing discontent with Dutch gang life, up until the actual departure of several members. Specific attention will be drawn to the methods, motives, and consequences of leaving this Dutch "gang" and the role of disillusionment in the process of disengagement.Younger members encountered a lack of financial compensation for the work they put in for the gang, which on the long run outweighed the benefits associated with being in the gang. Contrary to popular gang myths, most Dutch members cut ties with the gang abruptly and left without any repercussions. The importance of contextualized accounts of gang desistance and disengagement is highlighted, with specific attention to alternatives for gang life and the difficulties related to identity in the process of disengagement.